What's in a name? The quest for new metaphors for second language acquisition - Paiva,Vera Lucia Menezes Oliveira e (2014)
The present article focuses on a series of metaphors found in texts on language and language learning, and discusses the criticisms of the acquisition metaphor and the addition of participation as a new concept to represent language learning. The main theoretical proposals for second language acquisition (SLA) have been selected in order to verify which theories use acquisition and which use participation. While scrutinizing those texts, I found that other metaphors have also been proposed; however, acquisition and participation are still the most prevalent. Participation has been used as a metaphor since Sfard (1998) and has been well accepted in Applied Linguistics. Therefore, I present the cognitive view of metaphor and metonymy and demonstrate that, according to the cognitive studies on metaphor, participation cannot be seen as a metaphor, but rather as a metonym. To prove this, I use the metonymic model proposed by Lakoff (1990) as support. I conclude, agreeing with Ortega (2009) that a metaphorical polyphony can help us understand the complex phenomenon of language and language learning. Nevertheless, metonyms must not be disregarded.